An efficient hybrid detection algorithm for a full rate quasi-orthogonal prolonged MIMO MC-CDMA systems - Sayadi, F.; Ismail, M.; Misran, N.; Jumari, K.; Abdullah, M. (2009 IEEE 9th Malaysia International Conference on Communications, 2009)
Multiple-Input Multiple-Output (MIMO) antennas and Multi-Carrier Code Division Multiple Access (MC-CDMA) are very promising candidates for simultaneous utilize in 4G systems, since they attain robustness, high spectral efficiency, and high data rates in rich scattering environments. This paper proposes an efficient hybrid detection algorithm for downlink MC-CDMA system based on Orthogonal Frequency Division Multiplexing (OFDM). The proposed algorithm combines Energy Spreading Transform (EST) technique and the iterative architecture pilot based Minimum Mean Square Error (MMSE) channel estimation as well as Modified Projection Approximation Subspace Tracking Deflation (MPASTD) method, so called Hybrid EST Iterative MMSE-MPASTD (HEIMM) algorithm. The HEIMM algorithm contributes steadfastly to an accurate system design and evaluation with full rate mode in a space-frequency format of extended multiple antennas method also in the framework of a practical MC-CDMA system. Beneath high order modulation, the simulation results are presented to exhibit an improved Bit Error Rate (BER) performance with reduced-rank computational complexity that independent of different system loading.